(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This paper addresses the critical challenge of providing reliable, continuous, and sustainable electricity to off-grid consumers in remote and arid geographical locations. Conventional solar photovoltaic (PV) systems suffer from low efficiency and degradation under high operating temperatures, while standalone thermal systems exhibit low thermodynamic utilization. To overcome these limitations, this study proposes and optimizes an autonomous power supply system based on a Combined Solar Concentrator Thermoelectric Generator (CSC-TEG) architecture. A comprehensive mathematical and thermodynamic model is developed to evaluate the coupled fluid-thermal-electrical behavior of the system. The optimization framework integrates optical concentration ratios (Сr), geometric configurations of bismuth telluride (Bi2Te3) thermoelectric modules, and dynamic coolin strategies. Simulation results, validated through localized climatic datasets characteristic of continental arid zones, demonstrate that the optimized CSC-TEG system achieves a peak electrical efficiency enhancement of 18.4% compared to non-concentrating configurations. Furthermore, the integration of a phase-change material (PCM) based thermal storage buffer ensures a stable shift in power delivery during peak nocturnal demand periods. The financial assessment reveals a Levelized Cost of Energy (LCOE) reduction to 0.12/kWh, making it a highly viable alternative to diesel generation for remote applications. Keywords: Solar Concentrator, Thermoelectric Generator (TEG), Autonomous Power Supply, Remote Consumers,